Parceling in the text of a historical novel – rational method (Eurasian Journal of Philology Science and Education, 2020)
This article covers the questions of unique features of syntactic structures of the text of a historical novel. One thing that identifies the style of a writer is the syntactic structures he or she uses. One of the syntactic-stylistic methods that are used in the texts of historical novels is parceling. Parceling is the separation of phrases (sentences, phrases) using a word or a text that is closely connected to it. Correct and adequate interpretation of a written text depends on a high level of intellectual and emotional activity of a receiver. That is why the emotional condition of a recipient is a part of pragmatic parameters when it comes to linguistic researches in the modern pragmatic aspect of it. Showing one of Universe’s images, the mental world of a person is shown through his or her speech that needs a communicativepragmatic approach in the process of analysis of historical novels. In M. Magauyin’s work, there is a stress that is put on a certain situation with the help of parceling. For instance, Oraz-Mukhamed looked at calmly walking Ai-Sheshek, on his left. Only her shadow is visible. Soundless.Motionless. Only her horse is trying to catch up with her. The headshaking makes the impatience visible. The squad was slowly walking behind.